Silverstar (2025)
The following project is a proposal for the development of a 2D animated series. It includes a script for a pilot episode. This document will also present details, locations, and characters that strengthen the series' universe, from future allies to central villains. Although general details of the series will be discussed, all aspects of the script, financing, and production will focus solely on the pilot episode.